DELINQUENCY INPELAYANAN SOSIAL MARSUDI PUTRA (PSMP) TENGKU YUK KOTA PEKANBARU - Suci Adinda; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research conducted in Pelayanan Sosial Marsudi Putra (PSMP) Tengku Yuk Kota Pekanbaru. The purpose of this study was to determine the Causes of Juvenile Delinquency In Kota Pekanbaru. The research titled “Delinquency In Pelayanan Sosial Marsudi Putra (PSMP) Tengku Yuk Kota Pekanbaru”. Topics focus of this research is what kind of juvenile delinquency conducted in Kota Pekanbaru. Because there is no exact data on the number of juvenile delinquency in Kota Pekanbaru, authors use the technique in non probability. The subject was done by purposive sampling or intentionally election considerations is the subject of a teenage actor in Kota Pekanbaru. Instruments Data were observation, interviews and documentation. From research conducted, the authors found that the types of juvenile delinquency in Kota Pekanbaru is as follows: fighting, smoking, drinking, skipping school, and drugs. The background factors adolescent mischief is as follows: the family, the perception of adolescents to education, self-control is weak, the influence of friends, neighborhood and media. Crimes committed by juveniles in Kota Pekanbaru encouraged because of the lack of attention from parents and the environment on children's growth and cultivation of religious values from the environment in which children grow and develop. Keywords: Delinquency, Juvenile Delinquency Type